A Multigene Approach for Comparing Genealogy of Betacoronavirus from Cattle and Horses - Iracema N. Barros; Sheila O. S. Silva; Francisco S. Nogueira Neto; Karen M. Asano; Sibele P. Souza; Leonardo J. Richtzenhain; Paulo E. Brandao (The Scientific World Journal)
Gastroenteritis is one of the leading causes of morbidity and mortality among young and newborn animals and is often caused by multiple intestinal infections, with rotavirus and bovine coronavirus (BCoV) being the main viral causes in cattle. Given that BCoV is better studied than equine coronaviruses and given the possibility of interspecies transmission of these viruses, this research was designed to compare the partial sequences of the spike glycoprotein (S), hemagglutinin-esterase protein (HE), and nucleoprotein (N) genes from coronaviruses from adult cattle with winter dysentery, calves with neonatal diarrhea, and horses. To achieve this, eleven fecal samples from dairy cows with winter dysentery, three from calves, and two from horses, all from Brazil, were analysed. It could be concluded that the enteric BCoV genealogy from newborn and adult cattle is directly associated with geographic distribution patterns, when S and HE genes are taken into account. A less-resolved genealogy exists for the HE and N genes in cattle, with a trend for an age-related segregation pattern. The coronavirus strains from horses revealed Betacoronavirus sequences indistinguishable from those found in cattle, a fact previously unknown.